2012
DOI: 10.1002/rsa.20458
|View full text |Cite
|
Sign up to set email alerts
|

Graph bootstrap percolation

Abstract: Abstract. Graph bootstrap percolation is a deterministic cellular automaton which was introduced by Bollobás in 1968, and is defined as follows. Given a graph H, and a set G ⊂ E(K n ) of initially 'infected' edges, we infect, at each time step, a new edge e if there is a copy of H in K n such that e is the only not-yet infected edge of H. We say that G percolates in the H-bootstrap process if eventually every edge of K n is infected. The extremal questions for this model, when H is the complete graph K r , wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(126 citation statements)
references
References 31 publications
2
79
0
Order By: Relevance
“…For now, we write k = k − . The proof is identical to the proof of Lemma 3.3 down to equation (8). The case a + b ≥ 24 p remains unchanged (and that is the case which determines k).…”
mentioning
confidence: 75%
“…For now, we write k = k − . The proof is identical to the proof of Lemma 3.3 down to equation (8). The case a + b ≥ 24 p remains unchanged (and that is the case which determines k).…”
mentioning
confidence: 75%
“…A simple variation which leads to complex dynamics is to change the rules for nodes to burn. As in graph bootstrap percolation [3], the rules could be varied so nodes burn only if they are adjacent to at least r burned neighbors, where r > 1. We plan on studying this variation in future work.…”
Section: Discussionmentioning
confidence: 99%
“…, x k ) is called a burning sequence for G. With this notation, the burning number of G is the length of a shortest burning sequence for G; such a burning sequence is referred to as optimal. For example, for the path P 4 with node set {v 1 , v 2 , v 3 , v 4 }, the sequence (v 2 , v 4 ) is an optimal burning sequence; see Figure 1. Note that for a graph G with at least two nodes, we have that b(G) ≥ 2.…”
Section: Supported By Grants From Nsercmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that our lower bound holds as long as G ( n, p ) is weakly K s ‐saturated in K n . This problem was studied by Balogh, Bollobás and Morris , who showed that the probability threshold for G ( n, p ) to be weakly K s ‐saturated is around pn1/λ(s)polylog n, where λ(s)=true(s2true)2s2. It might be possible that wsat(G(n,p),Ks) changes its behavior at the same threshold.…”
Section: Discussionmentioning
confidence: 99%